2020
DOI: 10.1038/s41598-020-76357-y
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is positively related and tobacco smoking and alcohol consumption are negatively related to an increased risk of thyroid cancer

Abstract: The purpose of this study was to evaluate the relationships of smoking, alcohol consumption, and obesity with thyroid cancer in Korean residents. The Korean National Health Insurance Service-Health Screening Cohort includes individuals ≥ 40 years who were assessed from 2002 to 2013. In total, 4977 thyroid cancer participants were matched with respect to age, sex, income, and region of residence with 19,908 controls at a ratio of 1:4. Crude and adjusted (for the Charlson comorbidity index, smoking status, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…The diagnosis of thyroid cancer was referred to as participants with ICD-10 code C73 (malignant neoplasm of the thyroid gland) and treatment claim codes for thyroidectomy (P4551, P4552, P4553, P4554, and P4561) 6 , 7 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of thyroid cancer was referred to as participants with ICD-10 code C73 (malignant neoplasm of the thyroid gland) and treatment claim codes for thyroidectomy (P4551, P4552, P4553, P4554, and P4561) 6 , 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have postulated that overidentification or overdiagnosis of clinically occult, asymptomatic tumors as well as recent advancements in diagnostic technologies are responsible for the increase 4 , 5 . However, it is likely that other factors, such as environmental factors, lifestyle, family history and comorbidities, have significant roles in thyroid cancer development 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“… 23 Another study showed that obesity was highly related to tobacco smoking. 24 Active and passive smoking are typically accompanied by increased weight, and smokers tend to be either obese or overweight. Furthermore, in our study, people with abdominal obesity were more likely to partake in smoking (38.9%); therefore, smoking may influence the development of metabolic disorders and induce the abnormal distribution of fat.…”
Section: Discussionmentioning
confidence: 99%
“…The Institutional Review Board waived the requirement for written informed consent. A detailed description of the Korean National Health Insurance Service-Health Screening Cohort data is provided elsewhere [ 18 ].…”
Section: Methodsmentioning
confidence: 99%